The development of trunk muscles in male wrestlers assessed by magnetic resonance imaging - Kubo, J.; Ohta, A.; Takahashi, H.; Kukidome, T.; Funato, K. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to compare the development of trunk musculature among elite, sub-elite, and elite junior wrestlers. The performance level of these groups, ordered highest to lowest, is as follows: Elite (n = 20), sub-elite (n = 25), and elite junior (n = 39). A magnetic resonance imaging device was used to measure the cross-sectional area (CSA) of the trunk muscles. The whole trunk muscle cross- sectional area (t-MCSA) of the elite group was significantly larger than that of the elite junior group (p < 0.05). The rectus abdominis muscle CSA of the elite group was significantly larger than that of the elite junior group (p < 0.01). The psoas major muscle CSA of the elite group was significantly larger than that of the Elite junior group (p < 0.05). There were no significant differences in the CSA of any of the trunk muscles between the elite and Sub-elite groups. In conclusion, compared with elite junior wrestlers, it is conceivable that a greater CSA of trunk flexors of elite wrestlers is one factor which supports increased performance.